Gambaran Perilaku Masyarakat Dalam Upaya Pencegahan Malaria - Anggun Triyoolanda; Putra Apriadi Siregar (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Malaria in Indonesia is still a public health problem. Based on a study conducted in 2022, there were 2,208 cases of malaria reported during the study period in North Sumatra. According to a report from the World Health Organization (WHO) in 2023, the Southeast Asian region, including North Sumatra, is still the region with the highest malaria cases in the world. In 2021, the Southeast Asian region accounts for 95% of the total malaria cases in the world. Purpose: This study aims to explore information about efforts to prevent malaria in the community in Sorkam Kanan Village, Sorkam Barat District, Tapanuli Tengah Regency. Method: This study uses a qualitative method with a phenomenological approach. The research informants were 9 people who were determined by the snowball technique, the informants consisted of 8 residents and 1 health worker from the Community Health Center who handled the Malaria program. Results: This study shows that efforts to prevent malaria by killing larvae and adult malaria mosquitoes through house spraying, larvaciding and biological control have never been carried out by the community because they think this is the responsibility of health workers. To prevent malaria mosquito bites for those who have a habit of being outside the house at night by wearing long-sleeved shirts, jackets and long gloves.